Expression analysis and study of KLK4 in benign and malignant breast tumours - Papachristopoulou, G.; Avgeris, M.; Scorilas, A. (Thromb Haemost, 2009)
The steroid hormone-regulated gene KLK4 (kallikrein 4) is a new member of the human kallikrein-related peptidase gene family. Up to date, studies report that KLK4 is differentially expressed in many tumours. The purpose of this study was the expression analysis and study of KLK4 in benign and malignant breast tumours. Total RNA was isolated from 16 benign and 45 malignant breast tissue specimens. After testing RNA quality, cDNA was prepared by reverse transcription. Highly sensitive quantitative real-time PCR method for KLK4 mRNA quantification was developed using the SYBR Green chemistry. GAPDH served as a housekeeping gene. Relative quantification analysis was performed using the comparative C(T) method 2(-DeltaDeltaC)(T) KLK4 expression was found to vary in both patients' cohorts; however, a statistically significant elevation of the KLK4 mRNA levels was observed in malignant compared to benign tumour patients. Low KLK4 expression levels were found in well-differentiated tumours (p = 0.011) as well as in stage I (p = 0.024) patients. Moreover, a statistically significant (r(s) = -0.318, p = 0.035) negative correlation between the KLK4 expression and progesterone receptor staining was observed. ROC and logistic regression analysis recommended that KLK4 gene expression may be used as a new potential biomarker in breast cancer.
Keywords: *Gene Expression Regulation, Enzymologic; *Gene Expression Regulation, Neoplastic; Adult; Aged; Aged, 80 and over; Biomarkers, Tumor/*genetics; Breast Neoplasms/enzymology/*genetics/pathology; Carcinoma, Ductal, Breast/enzymology/*genetics/pathology; Cell Differentiation; Cell Line, Tumor; Female; Humans; Kallikreins/*genetics; Logistic Models; Male; Middle Aged; Neoplasm Staging; Odds Ratio; Prognosis; Receptors, Progesterone/analysis; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger/analysis; ROC Curve; Up-Regulation; Young Adult